THE CONCEPT OF NATIONALIZATION OF NADJAMOEDDIN DAENG MALEWA IN SOUTH SULAWESI ON 1907-1947 - Junaeda, Siti (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2011)
The ideas of Nationalism in South Sulawesi were marked by the incorporation of national organizations that have formed branches in Makasar. Makasar was not only a city of the center of administration or the center of politics, but also as a barometer for the eastern Indoneisa areas to be a designated area of various national organizations. Sarekat Isalm was the first modern organization built in Makasar in the 1916, followed by Muhammadiyah, Assiratal Mustaqim, NU, PKI, PNI, PARTINDO, PARINDRA et cetera. Apart from being the designation of the national organization to open their chapters, in South Sulawesi have appeared regional organizations, such as the Celebes Organization, which then transformed into Celebes Party, and South Celebes Organization. The utilization and translation of ideas of nationalism in South Sulawesi can be traces from the principles or working program for each and every organization.Nadjamoeddin is one of the moving figures in South Sulawesi who has actively participated in the expansion of the idea of nationalism and nationality by being active in local or national organizations of political party. He has build unity in realizing the national movement through organization or local and national parties such as Celebes Organization, Celebes Party, Parindra, dan South Celebes Party. In a few of his writings and speeches he believes that in order to achieve prosperity for the whole Sulawesi people particularly and Indonesia in general, and therefore there are three important things to attain. First: The unity of any and all nations; Second: Equal education for all; and Third: A strong economic system. Three of these matters have become the important conditions to achieve a strong and independent country.Â